ANALYSIS OF INCOME FACTORS FOR URUNG KETUPAT CRAFTSMAN DURING THE COVID-19 PANDEMIC AS A VOCATIONAL SCHOOL TEACHING MATERIAL - Supriyanto, Supriyanto; Junaidy, Ahmad Aldy; Harahap, Alfi Fadhilah Hakim; Permatasari, Melly Agustina (International Conference On Social Science Education, 2023)
This study aims to find out and analyze the factors that influence the income of urung ketupat craftsmen during the covid-19 pandemic as a supplement for teaching materials for class xi high school. This study uses a qualitative approach and descriptive research with primary data sources. The results showed that 1) the business capital factor was the main factor in the activities of urung ketupat craftsmen, 2) the raw material was palm leaves, 3) the labour for production activities used daily freelancers, 4) government policies such as (a ) social distancing keeps the distance between sellers and buyers (b) Large-scale Social Restrictions (PSBB) results in reduced productivity of working hours, (c) Enforcement of Community Activity Restrictions (PPKM), is the most influencing factor because wedding receptions are prohibited, more diamonds are ordered for that matter. (5) a description of the declining income of urung ketupat craftsmen can be used as local teaching materials in class XI SMK.